Strengthening road construction to support fishermen community activities in Belawan Fisherman village - Handana, Muhammad Agung Putra; Syahrizal; Siregar, Riza Inanda; Kamal (Talenta Publisher, 2019)
The school garden can be used for planting various types of plants. So that the use of land is more optimal, then one of the efforts that can be done is to invite students to plant various types of plants, such as vegetables, ornamental plants and fruits as well as medicinal plants. These plants can be placed in the school garden, both in the front and in the back. This activity aims to provide environmental education for early childhood through planting various types of plants and introducing various types of plants in early childhood. There are some Stages of activities, namely: preparation of planting media, planting, and harvesting of fast-growing type of vegetables. Based on the results of the activities, that the children are very enthusiastic and very happy through planting various types of plants in their school grounds.